2005
DOI: 10.1073/pnas.0500756102
|View full text |Cite
|
Sign up to set email alerts
|

An integrated functional genomics and metabolomics approach for defining poor prognosis in human neuroendocrine cancers

Abstract: Human neuroendocrine (NE) cancers range from relatively indolent to highly aggressive. In this study, we combine functional genomics with metabolomics to identify features of NE cancers associated with a poor outcome. Analysis of GeneChip datasets of primary prostate tumors, as well as lymph node and liver metastases from transgenic mice with a NE cell cancer, plus derived NE cell lines yielded a signature of 446 genes whose expression is enriched in neoplastic mouse prostatic NE cells. This signature was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
85
0
6

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(93 citation statements)
references
References 57 publications
(55 reference statements)
2
85
0
6
Order By: Relevance
“…1A), validating our previous LC͞MS studies (8). In addition to GABA, 1,2-propanediol (propylene glycol) was identified as another abundant metabolite (Fig.…”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations
“…1A), validating our previous LC͞MS studies (8). In addition to GABA, 1,2-propanediol (propylene glycol) was identified as another abundant metabolite (Fig.…”
Section: Resultssupporting
confidence: 71%
“…The results indicated that a distinguishing feature of poor prognosis NE tumors is a glutamic acid decarboxylase 1 (Gad1)-independent pathway for synthesis of GABA that uses the diamine oxidase, amiloride-binding protein 1 (Abp1). Follow-up GC-MS and LC-MS analyses and electrophysiological studies disclosed that PNEC cells synthesized GABA and expressed functional GABA A receptors on their surface (8). These findings suggested a previously uncharacterized mechanism for cellular signaling in the NE cancer microenvironment.…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…It is worth mentioning that DDC is regarded as a general biomarker for neuroendocrine tumours (Gazdar et al, 1988;Gilbert et al, 1995;Ippolito et al, 2005). High DDC mRNA expression has been noticed in small-cell lung carcinoma (SCLC), neuroblastoma, and pheochromocytoma (Jensen et al, 1990;Gilbert et al, 1999;Uccella et al, 2006).…”
mentioning
confidence: 99%